Decontamination of mustard sulfur and VX by sodium percarbonate complexed with 1-acetylguanidine as a novel activator. (17th December 2022) - Qi, Lihong; Xiao, Boren; Kong, Lingce; Xu, Yong; Yang, Jinxing; Zuo, Guomin
Abstract: The peroxide-based decontaminants had attracted great attention for degradation of chemical warfare agents (CWAs) because of their high performance, non-corrosive and environmental-friendly merits. Hydrogen peroxide can be activated by some organic activators to enhance the oxidation ability. In this work, a novel formula based on sodium percarbonate (SPC) complexed with 1-acetylguanidine (ACG) was investigated for decontamination of sulfur mustard (HD) and VX as CWAs. In the experimental results, the active species acetyl peroxide imide acid in the formula aqueous solution was detected in situ by Raman and 13 C NMR spectroscopy. The optimized conditions of the decontamination formula (SPC/ACG) were suggested that, the molar ratio of active oxygen and activator ([O]/[ACG]) was 1:1 while the pH value of the formula aqueous solution was about 9. To achieve the decontamination percentage over 99%, the molar ratio of active oxygen to CWA ((O)/(CWA)) needed to be at least 3 for HD and 7 for VX. Meanwhile, the degradation products detected by gas chromatography/mass spectrometry (GC/MS), liquid chromatography/mass spectrometry (LC/MS) and ion chromatography (IC) indicated that the oxidation and elimination reactions should have occurred on HD molecule, while the degradation of VX mainly originate from the nucleophilic substitution and oxidation reactions. HIGHLIGHT: activation mechanism; activation of hydrogen peroxide; advanced oxidation of chemical warfare agents; hazardous waste treatment; water treatment